OPTIMALISASI PEMBERANTASAN KORUPSI DI INDONESIA - Sitorus, Regina Syafriani Boru; Watonnah, Watonnah; Dewi, Ayu Efrita; Widiyani, Heni (Jurnal Pahlawan, 2023)
Action to eradicate corruption must be carried out comprehensively, integrally and holistically The commitment of law enforcement officials to consistently enforce the law and integrated is very important to ensure fair prosecution, provide legal certainty, and benefit the community This step will be carried out by imposing the most severe sanctions on perpetrators of corruption, including criminal sanctions with provisions for social sanctions, fines, compensation in the form of money, and return of evidence related to money laundering (TPPU) This not only increases the trust of citizens, This not only increases the trust of citizens, investors, and national pride, but also provides a deterrent effect, prevents potential perpetrators of corruption, optimizes the return of funds to the state and its people, and provides other positive impacts Corruption in Indonesia is a major obstacle to national economic development The government implements various strategies to eradicate corruption in Indonesia, but if one of them occurs, it will add 1000 more cases of corruption and spread it to various fields of life. Keyword : eradicating corruption enforcement corruption